The push strategy of product design knowledge in cloud environment with the multidimensional hierarchical context and SSA-BPNN model. (October 2022) - Zhao, Hang; Chen, Dengkai; Chen, Chen; Hou, Yuhong
Abstract: To assist designers in completing design tasks and improve the efficiency of product design, more and more design knowledge push approaches are coming about. With developments of information technology and cloud computing, knowledge service goes with the whole design process and it is represented by the knowledge push forming. The knowledge push is complex engineering, however, existing knowledge push approaches in traditional design patterns cannot exactly meet the personalized knowledge requirements of designers in cloud environment. To address this issue, we attempt to explore the push strategy of product design knowledge in cloud environment. Firstly, knowledge demands are analyzed with the multidimensional hierarchical context model and the design knowledge modeling is represented following characteristics of the cloud-based design pattern. Then, the knowledge push architecture contains the matching of knowledge to obtain alternative knowledge and the knowledge importance degree prediction with SSA-BPNN model to overcome the inaccuracy of judgments, which is put forward. Moreover, the push coefficient is calculated as the knowledge push reference. Eventually, an illustrative case of intelligent air conditioner product design in the cloud platform is taken to verify the application and performance of the proposed approach. We expect that this work could provide useful insights into the product design knowledge push in cloud environment.